PEMBERDAYAAN MAJELIS TA’LIM PEREMPUAN DALAM PERSPEKTIF MANAJEMEN DAKWAH - Basit, Abdul (Fakultas Dakwah IAIN Purwokerto, 2010)
Changes in society are so quick to have implications for the change of religiosity. These conditions demand achange in managing the activities of proselytizing, to more professional direction. One of the institutions that need to berevised is the women’s majelis taklim who have potential and significant role in life. Women’s majelis taklim need to bemanaged by using modern management with a way to empower both personal, institutional and social institutions. With theexpected empowerment, majelis taklim activities not only as a medium of learning and teaching community, but can playa role in addressing humanitarian problems that often befall women and also to improve the welfare of members.